CATALYTIC TECHNOLOGY FOR REDUCING THE CONTENT OF AROMATIC HYDROCARBONS IN MOTOR FUELS - Massenova Alma Tulegenovna; Kalykberdiyev Maksat Kuatovich; Sass Alexander Sergeevich; Kenzin Nail Rashidovich; Abilmagzhanov Arlan Zainutallaevich; Baiken Amankeldi (Academic Scientific Journal of Chemistry, 2019)
The aim of the work was to study the process of hydrodearomatization of diesel fractions for the production of environmentally friendly fuels with a low content of aromatic hydrocarbons. The hydrogenation of two diesel fractions 180-350°C and 230-360°C of PKOP LLP (PetroKazakhstanOilProducts, Shymkent) has been studied. Rh-Pt/Al2O3 catalysts were used in the work. The influence of the technological parameters of the process of hydrodearomatization (hydrogen pressure 2-6 MPa, temperature 100-220°C) on the reaction rate, conversion and aromatic hydrocarbon content at the “aniline point” was investigated. To increase stability and resistance to poisoning with sulfur-containing compounds of petroleum fractions, the carrier was modified with chromium oxide and synthetic zeolite ZSM-5, which led to an increase in the reaction rate and conversion of aromatic hydrocarbons. Optimal conditions have been selected (temperatures 200-220°C, hydrogen pressure 4-6 MPa, solvent - ethanol, propanol, isopropanol) for hydrogenation of diesel fractions 180-350°C and 230-360°C on Pt-Rh-catalysts supported on alumina and mixed carriers. The content of aromatic hydrocarbons was reduced by 10-20%. Some operational properties of diesel fuel (kinematic viscosity at 20°C, pour point and cloud point and density at 20°C) of the initial diesel fractions and after catalytic treatment were determined, the effect of temperature and pressure on the change in these characteristics was investigated.